Transgenerational memory of the effect of drought stress on wheat (Triticum aestivum L.) grain yield - Becheran, Daniela E.; Abeledo, Leonor Gabriela; Beznec, Ailin; Bossio, Adrian Ezequiel; Faccio, Paula Daniela; Miralles, Daniel J. (Springer, 2023)
Water deficit is one of the main abiotic stresses that affect wheat production worldwide. Plants exhibit phenotypic variations to mitigate the negative effects of water stress on grain yield. The objective of the work was to evaluate whether wheat (Triticum aestivum L.) plants showed transgenerational inheritance of environmental adaptation when exposed to water deficit around flowering (i.e. the critical phenological stage for the definition of grain yield). During the first experimental year, plants from three genotypes PIF: commercial cultivar; TR1 and TR4: transgenic genotypes derived from PIF containing the transcription unit PSARK::IPT (associated with the cytokinin-induced enhanced drought tolerance) were cultivated under well-watered (WWm) or water deficit from Z3.2 to Z6.9 + 5 days (WDm). Offspring of this first year were then grown under well-watered (WWo) or water deficit from Z3.2 to Z6.9 + 5 days (WDo) during the next two years, following a crop arrangement. Plants from seeds exposed to WDm tended to have a poor grain yield for both water regimes of the progeny (i.e. WWo and WDo) in both years. The number of grains per unit area was the numerical component that best explained grain yield (r2 = 0.98; p < 0.05), due to variations in the number of grains per ear. Grain weight was a highly conservative trait. Aboveground biomass and harvest index reduced in response to WDo compared to WWo and followed similar responses to grain yield. In conclusion, a restrictive maternal water environment worsened yield response in the following generation, independent of the water condition to which the offspring were exposed, due to reductions in the number of grains per spike, in total aboveground biomass at maturity, and in its partitioning to the grain.